iF concept award : yearbook 2010. (Hannover : International Forum Design, 2010)
Outstanding design deserves a distinctive presentation - the iF product design award yearbook 2010 introduces all of the winners of the coveted iF product design award. In 2010, the publication provides an exciting look at the sixteen categories Transportation Design, Leisure / Lifestyle, Audio / Video, Telecommunications, Computer, Office / Business, Lighting, Furniture / Home Textiles, Kitchen / Household, Bathroom / Wellness, Buildings, Public Design / Interior Design, Medicine / Health+Care, Industry / Skilled Trades, Special Vehicles / Construction / Agriculture, and Advanced Studies. Each award-winning entry is presented in images and text. A detailed index of manufacturers and designers facilitates the search for particular products. Thanks to striking and authentic photographs, the yearbook offers impressions of the jury's deliberations as well as expert opinions on the award-winning products themselves. The iF product design award yearbook 2010 is a user-friendly reference work for anyone with an interest in design and an informative archive for manufacturers, designers, and opinion makers from media, economy, and politics.